Brachytherapy for cervical cancer: from intracavitary to interstitial technique - Yang, Xiaojing; Ren, Hanru; Li, Zhen; Fu, Jie (Frontiers in Oncology, 2024)
Cervical cancer is a common malignant tumor of female reproductive system. Radiation therapy is one of the main methods of cervical cancer treatment, of which brachytherapy is an essential and important part of radiation therapy for locally advanced cervical cancer. With the rapid development of imaging technologies such as computed tomography (CT) and magnetic resonance imaging (MRI), brachytherapy for cervical cancer has gradually developed from traditional two-dimensional image-guided technology to three-dimensional image-guided technology. And there are more and more treatment methods, including intracavitary brachytherapy, interstitial brachytherapy, and intracavitary combined interstitial implantation brachytherapy. We performed a PubMed search for introduce the application progress of intracavity, implantation, intracavity combined implantation brachytherapy and radioactive seed implantation, and discuss the dosimetric feasibility of internal and external fusion irradiation.